POLA PERSEBARAN PASAK BUMI (Eurycoma longifolia Jack.) DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) UNIVERSITAS LAMBUNG MANGKURAT KALIMANTAN SELATAN - Zainal Arifin; Gusti Muhammad Hatta; Sulaiman Bakri (Jurnal Sylva Scienteae, 2021)
The purpose of this study is to analyze the distribution pattern of pasak bumi in Forest Areas with Special Purpose, Lambung Mangkurat University, South Kalimantan using mean variance ratio analysis.The research used plot which has five line observation and each line has 10 point observation, respectively.The line has 200 meters in length and 20 meters in width. Determination of the location of the data collection was done purposive sampling the location of the data collection was chosen based on information by the type identifier where there are peg earth plants in the KHDTK ULM South Kalimantan which were the object of the study. Based on observations in the field and using the mean ratio variance of the distribution patterns of the earth's stake in the KHDTK ULM, including the random category. The composition of trees around the location is dominated by madang puspa trees (Schima sp), wangun gunung (Melicope sp), tengkook ayam (Cryptocarya sp) and margatahan (Palaquium dasyphyllum)Keywords : Pasak Bumi; Distribution Patterns; KHDTK